2015
DOI: 10.1021/jo5027832
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Henry Reaction of Nitroalkanes and Aldehydes Catalyzed by a Chiral N,N-Dioxide/Cu(I) Complex

Abstract: An easily available N,N'-dioxide/Cu(I) complex has been developed for the catalytic asymmetric nitroaldol (Henry) reaction of aldehydes with nitroethane. Under mild reaction conditions, a series of substituted aromatic, heteroaromatic and α,β-unsaturated aldehydes are transformed to the corresponding anti-β-nitroalcohols in good to excellent yields (up to 99%) with moderate to good dr (up to 16.7:1 anti/syn) and high ee values (up to 97%). Besides nitroethane, nitromethane and 1-nitropropane were also employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 93 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Absolute and relative configuration of the target adducts 11a-11s and 11u was determined by comparison of 1 H NMR spectra and the relative elution order of resolved peaks with authentic samples and literature data. 12,[17][18][19][20][21][22][23] Absolute and relative configuration of 11t was assigned (S,S)-by analogy with other β-nitro alcohols. A standard septum capped 2-mL HPLC vial equipped with a small magnetic stirring bar was charged with (R a )-CAT or (S a )-CAT (7.5 mg; 10 µmol), an appropriate aldehyde (100 µmol) and dry THF (200 µL).…”
Section: Stereochemical Assignmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Absolute and relative configuration of the target adducts 11a-11s and 11u was determined by comparison of 1 H NMR spectra and the relative elution order of resolved peaks with authentic samples and literature data. 12,[17][18][19][20][21][22][23] Absolute and relative configuration of 11t was assigned (S,S)-by analogy with other β-nitro alcohols. A standard septum capped 2-mL HPLC vial equipped with a small magnetic stirring bar was charged with (R a )-CAT or (S a )-CAT (7.5 mg; 10 µmol), an appropriate aldehyde (100 µmol) and dry THF (200 µL).…”
Section: Stereochemical Assignmentsmentioning
confidence: 99%
“…(S a )$(+)$CAT)peak)Chiral HPLC chromatogram of (1R,2R)-11q ( i PrOH-Hp, 10:90, 0.5 mL/min; ee = 97%) purified by column chromatography (SiO 2 , Hp-EtOAc, 9:1).! 1-(3-fluorophenyl)-2-nitropropan-1-ol (11r)22 HPLC conditions: i PrOH-Hp, 20:80, 0.5 mL/min, 5 °C (λ = 230 nm). rac-11r was prepared according to GP 1 (isolated yield 86%) [Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Maheswaran, [23] O'Brien, [24] and our group [31] had shown that CuCl 2 complexes of the chiral bispidines 1 and 2 and of the tricyclic9 -oxabispidine 5 are effective catalystsf or asymmetricH enry (nitroaldol) reactions. [57,58] The b-nitro alcohols were formed in acceptable to excellent7 3-98 % ee,a lthought he catalyst loadings required (20 mol %) were relative-Scheme7.Synthesis of the tricyclic bispidine 10 a under simultaneous bispidine and pyrrolidinef ormation.…”
Section: Evaluation Of the New Bispidines In Asymmetric Synthesismentioning
confidence: 99%
“…Pedro and Blay first extended the Henry reactions to 2-acylpyridine N -oxides, which provided a convenient way for synthesizing β-amino tert -alcohols substructure bearing a quaternary stereocenter bonded to a 2-pyridyl moiety [40]. The asymmetric Henry reaction of 2-acylpyridine N -oxide remains a challenge as N -oxides generally act as competitive catalyst inhibitors or displace activating ligands (For examples of related asymmetric Henry reaction using N -oxides as ligands, see ref [22,41,42,43]). We recently reported an asymmetric Henry reaction of 2-acylpyridine N -oxides catalyzed by a pre-prepared Ni-PyBisulidine complex, and the corresponding results are not satisfactory [23].…”
Section: Introductionmentioning
confidence: 99%